Systemic-pulmonary collateral supply associated with clinical severity of chronic thromboembolic pulmonary hypertension: a study using intra-aortic computed tomography angiography. - Sun, Wenyu; Ota, Hideki; Sato, Haruka; Yamamoto, Saori; Tatebe, Shunsuke; Aoki, Tatsuo; Sugimura, Koichiro; Tominaga, Junya; Shimokawa, Hiroaki; Ueda, Takuya; Takase, Kei (European Radiology, 2022)
Objectives: To assess whether systemic-pulmonary collaterals are associated with clinical severity and extent of pulmonary perfusion defects in chronic thromboembolic pulmonary hypertension (CTEPH).Methods: This prospective study was approved by a local ethics committee. Twenty-four patients diagnosed with inoperable CTEPH were enrolled between July 2014 and February 2017. Systemic-pulmonary collaterals were detected using pulmonary vascular enhancement on intra-aortic computed tomography (CT) angiography. The pulmonary enhancement parameters were calculated, including (1) Hounsfield unit differences (HUdiff) between pulmonary trunks and pulmonary arteries (PAs) or veins (PVs), namely HUdiff-PA and HUdiff-PV, on the segmental base; (2) the mean HUdiff-PA, mean HUdiff-PV, numbers of significantly enhanced PAs and PVs, on the patient base. Pulmonary perfusion defects were recorded and scored using the lung perfused blood volume (PBV) based on intravenous dual-energy CT (DECT) angiography. Pearson's or Spearman's correlation coefficients were used to evaluate correlations between the following: (1) segment-based intra-aortic CT and intravenous DECT parameters (2) patient-based intra-aortic CT parameters and clinical severity parameters or lung PBV scores. Statistical significance was set at p < 0.05.Results: Segmental HUdiff-PV was correlated with the segmental perfusion defect score (r = 0.45, p < 0.01). The mean HUdiff-PV was correlated with the mean pulmonary arterial pressure (PAP) (r = 0.52, p < 0.01), cardiac output (rho = - 0.41, p = 0.05), and lung PBV score (rho = 0.43, p = 0.04). And the number of significantly enhanced PVs was correlated with the mean PAP (r = 0.54, p < 0.01), pulmonary vascular resistance (r = 0.54, p < 0.01), and lung PBV score (rho = 0.50, p = 0.01).Conclusions: PV enhancement measured by intra-aortic CT angiography reflects clinical severity and pulmonary perfusion defects in CTEPH.Key Points: • Intra-aortic CT angiography demonstrated heterogeneous enhancement within the pulmonary vasculature, showing collaterals from the systemic arteries to the pulmonary circulation in CTEPH. • The degree of systemic-pulmonary collateral development was significantly correlated with the clinical severity of CTEPH and may be used to evaluate disease progression. • The distribution of systemic-pulmonary collaterals is positively correlated with perfusion defects in the lung segments in CTEPH.